EFEKTIVITAS PROBIOTIK BACILLUS SPP. TERHADAP PERFORMAN AYAM RAS PEDAGING - Muh. Nur Hidayat (Teknosains, 2013)
The aim of this research is to know effect of introduced Bacillus spp. as probiotic on the performance of broiler. This research carried out at Laboratory of Poultry Production, Laboratory of Husbandry Pshyology, and Laboratory of Chemichal Husbadry Nutrition Faculty of Husbandry Hasanuddin University, Makassar. This research was based on Randomized Complit Design (RCD) with four replications and treatments, each replications consist of four day old chicken (d.o.c). Treatments were consisted of fourth: (1) Basal feed (negative control) (2) Basal feed + zinc bacitracin 50 mg/kg feed (positive control) (3) Basal feed+ Bacillus spp. with 50 mg/kg feed (8x108 CFU), and (4) Basal feed + Bacillus spp. with 60 mg/kg feed (11.2x108 CFU). Data were analyzed with Analysis of Variance and continued by test Duncan. The result of this research, Bacillus spp. as probiotic significantly effect of feed consumption, wight again, and feed conversion (P<0.05). Bacillus spp. can use as probiotic into poultry feed for decrease used antbiobitic to improve broilers performance.